Pengaruh Model Contextual Teaching Learning Berbasis Tri Hita Karana Terhadap Kemampuan Berpikir Kritis Dan Hasil Belajar: The Effect of the Tri Hita Karana-Based Contextual Teaching and Learning Model on Critical Thinking Skills and Learning Outcomes - Budiartini, Ni Nyoman; Lisna Handayani, Ni Nyoman; Gede Hadriani, Ni Luh (Institut Agama Islam Daruttaqwa Gresik, 2025)
Learning in elementary schools of Natural and Social Sciences remains teacher-centered and fails to apply innovative methods, thereby affecting students' low critical thinking skills and learning outcomes. This study aims to analyze the effects of the Tri Hita Karana-based Contextual Teaching and Learning model on critical thinking skills and learning outcomes of fifth-grade students at Elementary School Cluster IX, Buleleng District, both partially and simultaneously. This study used a post-test-only control-group Design. The sampling technique used was random sampling. The sample for this study consisted of 51 students. The data collection technique used an essay test for critical thinking skills and a multiple-choice test for social studies learning outcomes. The data analysis technique used was Multivariate Analysis of Variance (MANOVA). The results of the study showed that 1) there were significant differences in critical thinking skills between groups of students who followed the Tri Hita Karana-based Contextual Teaching Learning model and groups of students who followed conventional learning; 2) there were significant differences in social studies learning outcomes between groups of students who followed the Tri Hita Karana-based Contextual Teaching Learning model and groups of students who followed conventional learning; 3) there were significant simultaneous differences in critical thinking skills and social studies learning outcomes between groups of students who followed the Tri Hita Karana-based Contextual Teaching Learning model and groups of students who followed conventional learning.